Government Expenditure in Suriname: A Stimulus or Impediment to Growth - Albert Mungroo; Gavin Ooft; Peggy Tjon Kie Sim-Balker (Centrale Bank van Suriname, 2014)
This paper examines the relationship between government expenditures and economic growth in Suriname from 1971 to 2011. According to the Keynesian theory it is the government's responsibility to stimulate or dampen economic growth within the country by using fiscal policy. For the last decade Suriname has experienced sustained economic growth. Some schools of economic thought argue that government expenditure has a positive effect in prolonging and sustaining growth while others disagree. A Dynamic Ordinary Least Square method is used to examine the effects of the different components of government expenditure on economic growth. Capital expenditure and subsidies & transfer are found to stimulate growth, while wages & salaries and goods & services impede growth in the long run.
Additional information: The views expressed in this research paper are those of the authors and do not necessarily represent those of the Centrale Bank van Suriname. Research papers describe research in progress by the authors and are published to elicit comments and to further debate.
Keywords: E62; O4; C22; 330; Fiscal Policy; Economic Growth; Linear Regression